The Ukrainian (post)revolutionary processes: - Lapshyna, Iryna (2021)
This paper explores the Ukrainian diaspora mobilisation in the UK and Poland in the aftermath of the Euromaidan and the Russian aggression from the end of 2013. It examines the two referred case studies of the Ukrainian diaspora and focusses specifically on the interaction between the mobilisations of old and new diasporas, the formation of new Ukrainian “diasporic communities”, and the diaspora contribution to homeland development. The literature on social movements shows that transnational diasporic mobilisations in the UK and Poland may be seen as “extensions” of the Euromaidan social movement in Ukraine. The empirical data shows that the Ukrainian diasporic communities in both countries have united and grown stronger due to the events in Ukraine. The communities have been engaged in development activities of different forms contributing with their resources and skills to bring about social, economic, and political support in their homeland. Moreover, diasporic communities in both countries claim to be recognised by the national government as important actors. The article concludes that the Ukrainian diaspora has the desire, motive, opportunity and means to engage in transnational activities, at least for the time being, which makes it an active diaspora.